Causes and Consequences of COVID-19-Associated Bacterial Infections - Farrell, Jennifer M.; Zhao, Conan Y.; Tarquinio, Keiko M.; Brown, Sam P. (Frontiers in Microbiology, 2021)
The COVID-19 literature highlights that bacterial infections are more common in fatal cases than recovered cases. If bacterial infections drive mortality in COVID-19, this has clear implications for patient management. However, it is possible that the enrichment of bacterial infections in COVID-19 fatalities is simply a by-product of late-stage pathology, leading to different advice for patient management. To address this question, we review current knowledge on bacterial infections in COVID-19, assess information from past viral respiratory pandemics, and simulate alternate causal models of interactions between virus, bacteria, and mortality in COVID-19. From these models, we conclude that currently available data is not sufficient to discriminate between these alternate causal pathways, and highlight what data is required to determine the relative contribution of bacterial infection to COVID-19 morbidity and mortality. We further summarize the potential long-term consequences of SARS-CoV-2 infection.